2022
DOI: 10.3389/fsurg.2022.1006194
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic and open approach in the treatment of heterotopic pregnancy following embryo transfer

Abstract: PurposeHeterotopic pregnancy (HP) is a rare disease with the coexistence of an intrauterine and ectopic embryos. There is no consensus on the optimal treatment of HP at present. This research aimed to compare the perioperative and pregnancy outcomes of laparoscopic (LA) and open approach (OA) in patients with HP after embryo transfer.MethodsWomen with HP receiving surgical treatment (LA or OA) were retrospectively recruited in this study between October 2006 and December 2020. The demographic, perioperative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
0
5
0
2
Order By: Relevance
“…A growing body of literature has demonstrated that treating the extrauterine pregnancy via invasive surgery has no effect on the risk of miscarriage of the concomitant alive IUP. [17–20] Our study showed that the average pregnancy loss rate for HP within 2 weeks of surgery was 12.3% (13/106), which was similar to the 12% to 17% miscarriage rate reported in previous studies. [1,11,13,21,22] Moreover, considering that spontaneous abortion occurs in 11% to 65% of viable IUPs, surgical intervention for HP is considered safe and does not augment the risk factors for miscarriage of viable IUPs in patients with HP.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature has demonstrated that treating the extrauterine pregnancy via invasive surgery has no effect on the risk of miscarriage of the concomitant alive IUP. [17–20] Our study showed that the average pregnancy loss rate for HP within 2 weeks of surgery was 12.3% (13/106), which was similar to the 12% to 17% miscarriage rate reported in previous studies. [1,11,13,21,22] Moreover, considering that spontaneous abortion occurs in 11% to 65% of viable IUPs, surgical intervention for HP is considered safe and does not augment the risk factors for miscarriage of viable IUPs in patients with HP.…”
Section: Discussionmentioning
confidence: 99%
“…Expectant management has also been noted as a strategy to avoid potential complications related to surgery, with the transabdominal sonographic-guided aspiration of ectopic gestational embryos identified as having the best maternal outcome [ 13 ]. Furthermore, laparoscopic surgery has been reported as a safe and effective treatment for removing ectopic pregnancy without compromising the IUP [ 50 ]. These diverse findings contribute valuable insights into the nuanced considerations in managing multifetal pregnancies and HP, highlighting the importance of tailored approaches based on individual cases.…”
Section: Reviewmentioning
confidence: 99%
“…Depending on the specific clinical scenario, KCl dosing is subject to variation. For intravenous administration, the infusion rate should generally not exceed 10-20 mmol per hour, with higher rates potentially necessitating cardiac monitoring [49][50][51]. It is imperative to administer KCl via a volumetric infusion pump, and regular checks of the infusion site for redness and inflammation are recommended.…”
Section: Considerations For Choosing Kcl Infusionmentioning
confidence: 99%
“…În general, este recunoscut faptul că factorul de risc pentru apariția SH include: boli inflamatorii ale organelor pelvine, proces aderențial în bazinul mic, hidrosalpinx, antecedente de sarcini tubare, intervenții chirurgicale la trompele uterine, TRA [3,7,17]. Odată cu utilizarea pe scară largă a TRA, s-a observat că transferul de embrioni multipli este considerat un factor de risc major pentru apariția SH [18,19]. În același timp, ≈ 30% dintre pacientele cu SH nu au avut factori de risc [1,2,16].…”
Section: Introducereunclassified
“…(2020) au sugerat că evoluția normală a sarcinii intrauterine se observă indiferent de metodele de rezolvare a sarcinii ectopice -laparotomie sau laparoscopie [6]. Dovada acestei concluzii a fost un studiu din China, unde, la compararea intervențiilor laparoscopice (n=62) și laparotomice (n=24) pentru SH, s-a constatat că rata de finalizare a unei sarcini intrauterine cu o naștere cu copil viu a fost de 94% față de 96%, respectiv [19] . Cu toate acestea, într-un studiu realizat de Li J. și coaut., (2020), frecvența întreruperii sarcinii intrauterine după laparotomie a fost zero, după intervenții laparoscopice 22.2%, ceea ce a permis autorilor să spună că laparoscopia poate fi considerată ca un factor de risc potențial pentru avortul spontan [30].…”
Section: Introducereunclassified